Efficient bimetallic nanoparticles embedded-porous silicon CO gas sensor. (March 2019) - Alwan, Alwan M.; Hashim, Duaa A.; Jawad, Muslim F.
Highlights: Efficient control of NPs grain size within porous structure. Increase the surface area of the hybrid structure, this is most important for gas sensing properties. Development of bimetallic nanoparticles at very low cost of controlling on the morphological structure of the Psi surface. Abstract: In this study, the surface modification process involving the embedding of Au or Pd monometallic and AuPd bimetallic alloy nanoparticles within porous silicon-based gas sensor was investigated. Porous silicon layer (P-si) was prepared by photo electrochemical etching (PECE) by using 635 nm diode laser of 25 mW/cm 2 intensity. AuNPs/P-si, PdNPs/P-si and AuPdNPs/P-si hetero structures were prepared by ion reduction process. This was materialized dipping fresh P-si in a salt solution containing HAuCl4 and PdCl2 ; mixed at ratio 1:1 for about (1.2, 5 and 2 min), respectively. The heterostructures were investigated by utilizing scanning electron microscopy (SEM), FTIR analysis, X-ray diffraction (XRD) and energy dispersive X-ray analysis (EDS). Efficient gas sensing process was recorded for modified porous silicon (P-si) gas sensor with smallest bimetallic AuPd nanoparticles size. Considerable improvements were noticed in sensitivity and temporal response after incorporating the bimetallic AuPd nanoparticles into the silicon matrix as compared to bare P-si and monometallic nanoparticles gas sensors due to the high specific surface area and the higher value of the barrier height of AuPdNPs/P-si hetero structures.